Pendampingan Sertifikasi Halal Gratis 2025 Skema Self-Declare pada UMKM Kelurahan Sidosermo - Pramulia, Anggita; Iryanti, Endang (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Halal certification is a mandatory legality for food and beverage entrepreneurs to guarantee the safety and halal integrity of a product for Muslim consumers. Without an official certificate issued by the Halal Product Assurance Agency (BPJPH), products risk losing consumer trust. However, the phenomenon in Sidosermo Village, Surabaya, shows that many MSMEs have not yet obtained official certification and are using unofficial halal logos. This condition required intervention through free halal assistance under the self-declare scheme. This community service activity was conducted in five stages: preparation, legality survey, socialization of SIHALAL regulations, registration assistance, and monitoring the application until the certificate was issued. The results of this activity showed that 19 assisted MSMEs successfully obtained official halal certificates. Consequently, this community service is able to improve legal compliance, enhance entrepreneurs' understanding regarding the differences in official halal logos, and support the acceleration of national halal certification.